Process of Vendor Bill Payment - Indriyana Dewi (International Publisher, 2022)
The purpose of this study is to find out the vendor bill payment process, to find out the obstacles during the vendor bill payment process and to find solutions in dealing with obstacles during the vendor bill payment process. The research methodology used is Qualitative Descriptive which aims to describe the conditions and analyze the vendor bill payment process. In this study, data relating to the author's study are sourced from library studies, field studies, and documentation techniques. The results of the research on the Vendor Bill Payment Process are as follows: the vendor bill payment process at the company has been going well, starting from receiving Purchase Orders (POs) by finance staff and from purchasing staff to the finance & accounting director's signature on demand deposits and Multipurpose Forms. (FM) as an approval, payment will be made, and payment will be made by the finance supervisor. Constraints that occur during the vendor bill payment process can be overcome by fairly good solutions to the obstacles encountered, ranging from problems when receiving documents provided by purchasing staff, which are often not in accordance with the attachments or incomplete documents, staff inaccuracies. finance at the time of data input, the lack of information obtained regarding the presence of new employees or vendors, and the use of systems that have not been effective. The company's solutions to problems during the vendor bill payment process have been able to resolve existing problems in accordance with the stages of the bill payment process, but require cooperation from the relevant divisions.